Методи та моделі нейромережевої апроксимації градуювальних характеристик NTC-термісторів - Fedin, Serhii; Zubretska, Irina (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2022)
The hypothesis about the expediency of using RBF-networks to improve the accuracy of constructing the calibration characteristics of NTC-thermistors in the operating temperature range without dividing it into subranges is confirmed. It has been established that the error of the neural network approximation of the calibration characteristics of NTC-thermistors based on RBF-networks is at least one and a half times less than the permissible error of approximation of the third-order polynomial model, which is used in the software of modern systems for collecting and processing measurement information. A technique has been developed for processing measurement information using adaptive RBF-networks to automate constructing individual calibration characteristics and periodic calibration of NTC-thermistors.